Pengenalan Senam Pernapasan Yoga Pada Masyarakat Desa Pulubala Kecamatan Pulubala Kabupaten Gorontalo - Lamusu, Zulkifli; Podungge, Risna; Mile, Sarjan (Universitas Negeri Gorontalo, 2024)
The purpose of community service activities carried out in Pulubala village is to socialize tips in increasing endurance through yoga respiratory Gymnastics for health. The benefits of this socialization activity can directly contribute science and skills for the people of Pulubala Village, Gorontalo Regency in maintaining their health and increasing their endurance through yoga breathing Gymnastics techniques that will be taught. Furthermore, the benefits for the lecturer are as a form of science contribution to the community in terms of the implementation of the Tri Dharma of Higher Education in the form of Community Service. The method of community service implementation includes lectures, questions and answers and demonstrations. The evaluation of this activity is the community's understanding and ability to perform yoga breathing exercises through feedback from the community through the activities that have been implemented. Holding group practice sessions regularly for several days to ensure that people really understand and are able to do yoga breathing exercise techniques correctly. Positive feedback from the community regarding the benefits felt after participating in socialization activities and practicing yoga breathing exercises.